Open economy macroeconomics - Uribe, Martin; Schmitt-Grohe, Stephanie (Princeton, NJ Princeton University Press, 2017)
"Combining theoretical models and data in ways unimaginable just a few years ago, open economy macroeconomics has experienced enormous growth over the past several decades. This rigorous and self-contained textbook brings graduate students, scholars, and policymakers to the research frontier and provides the tools and context necessary for new research and policy proposals. Martâin Uribe and Stephanie Schmitt-Grohâe factor in the discipline's latest developments, including major theoretical advances in incorporating financial and nominal frictions into microfounded dynamic models of the open economy, the availability of macro- and microdata for emerging and developed countries, and a revolution in the tools available to simulate and estimate dynamic stochastic models. The authors begin with a canonical general equilibrium model of an open economy and then build levels of complexity through the coverage of important topics such as international business-cycle analysis, financial frictions as drivers and transmitters of business cycles and global crises, sovereign default, pecuniary externalities, involuntary unemployment, optimal macroprudential policy, and the role of nominal rigidities in shaping optimal exchange-rate policy. Based on courses taught at several universities, Open Economy Macroeconomics is an essential resource for students, researchers, and practitioners. Detailed exploration of international business-cycle analysis Coverage of financial frictions as drivers and transmitters of business cycles and global crises Extensive investigation of nominal rigidities and their role in shaping optimal exchange-rate policy Other topics include fixed exchange-rate regimes, involuntary unemployment, optimal macroprudential policy, and sovereign default and debt sustainability Chapters include exercises and replication codes "--Provided by publisher.
Includes bibliographical references (pages 591-600) and index.
Keywords: Macroeconomics; Economic policy; Political planning; Business and economics -- Macroeconomics; Business and economics -- Theory